Information behaviour of migrant Hispanic farm workers and their families in the Pacific Northwest Information grounds, Information behaviour, Behavior, Washington, Immigrants, Information habits - Karen E. Fisher; Elizabeth Marcoux; Lupine S. Miller; Agueda Sánchez; Eva Ramirez Cunningham (Information Research: An International Electronic Journal)
Immigrants are generally perceived to be information poor, meaning they face major challenges with finding and using greatly needed everyday information. However, little research exists from an information behaviour perspective as differences in language, culture, and other factors such as access make immigrants a difficult population to study. We explored the everyday information behaviour and information grounds of migrant Hispanic farm workers through field observation and interviews with users, non-users, and staff of community technology centres in a major agricultural area. Findings suggest that personal networks having various levels of credibility were used more readily than any other type of information source. Credibility and use of various sources seemed to relate to personal status as well as interest in information.